BIOLOGICAL CONTROL OF GYPSY MOTH (LYMANTRIA DISPAR): AN RNAI-BASED APPROACH AND A CASE FOR DNA INSECTICIDES - Nyadar, Palmah M.; Zaitsev, Aleksei S.; Tajudeen, Adeyemi A.; Shumskykh, Maksym N.; Oberemok, Volodymyr V. (Archives of Biological Sciences, 2016)
The discovery of the post-transcriptional gene silencing (PTGS) mechanism, widely known as RNAi (RNA interference), has contributed towards the elucidation of the cellular machinery involved in the response against viral infections based on gene silencing, and in developmental regulation of translational suppression. The application of RNAi in insect pest management (IPM), and gene functional analysis, has been of enormous importance. Unfortunately, as RNAi has many times proven to be difficult to examine in Lepidoptera, focus has shifted to other potential post-genomic options in IPM. Special attention has afforded to novel DNA insecticides based on preparations of short single-stranded fragments of baculovirus anti-apoptosis genes, which represent a safe and relatively rapid alternative approach for IPM. This paper focuses on the drawbacks and advantages of DNA insecticides used in gypsy moth control and based on RNAi. Keywords: RNAi-based insect pest control; DNA insecticides; gypsy moth control Received: August 28, 2015; Revised: November 16, 2015; Accepted: November 20, 2015; Published online: May 5, 2016